How the information use environment influences search activities: A case of English primary schools. Issue 2 (6th March 2019) - Rutter, Sophie; Clough, Paul David; Toms, Elaine G.
Abstract : Purpose: The information use environment (IUE) – the context within which the search activity takes place – is critical to understanding the search process as this will affect how the value of information is determined. The purpose of this paper is to investigate what factors influence search in English primary schools (children aged 4–11) and how information found is subsequently used. Design/methodology/approach: Ten teachers, selected using maximal variation sampling, describe search-related activities within the classroom. The resulting interview data were analysed thematically for the influence of the environment on search and different information uses. The findings were then validated against three classroom observations. Findings: 12 categories of information use were identified, and 5 aspects of the environment (the national curriculum, best practice, different skills of children and teachers, keeping children safe, and limited time and resource) combine to influence and shape search in this setting. Research limitations/implications: Findings support the argument that it is the IUE that is the key influence of search activity. What makes children a distinct user group is linked to the environment within which they use information rather than age, as advocated in previous studies. Practical implications: The features of search systems and practical guidance for teachers and children should be designed to support information use within the IUE. Originality/value: As far as the authors are aware, this is the first study to consider the influence of the IUE on how search is enacted within primary schools.